New results on global exponential stability for a periodic Nicholson’s blowflies model involving time-varying delays - Qian Cao; Guoqiu Wang; Chaofan Qian (Advances in Difference Equations, 2020)
Abstract This paper investigates a periodic Nicholson’s blowflies equation with multiple time-varying delays. By using differential inequality techniques and the fluctuation lemma, we establish a criterion to ensure the global exponential stability on the positive solutions of the addressed equation, which improves and complements some existing ones. The effectiveness of the obtained result is illustrated by some numerical simulations.